A gene synthesis regime for Malaysia to emulate in securing future bioprinted vaccines - Marina Abdul Majid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The merger between synthetic biology and bioprinting will someday enable vaccines to be bioprinted utilising genetic material. Unregulated gene synthesis companies may unwittingly supply genetic material to a terrorist if there is no verification of purchasers’ personal identity and affiliation with a legitimate research organisation. This study has the objective of focusing on whether Malaysia regulates and conducts Deoxyribonucleic Acid (DNA) sequence screening among gene synthesis companies which are meant for bioprinting vaccines that can be misused for bioterrorism. This study is qualitative. Gene synthesis guidelines from the United States (US), the International Gene Synthesis Consortium (IGSC), the Nuclear Threat Initiative-World Economic Forum (NTI-WEF) Biosecurity Innovation and Risk Reduction report were referred as examples for changes in Malaysia’s draft National Code of Conduct for Biosecurity [thereafter known as Code]. These soft law documents constitute the regime for gene synthesis and a form of transnational new governance. The findings indicate that in the absence of a specific binding regulation, Malaysia’s draft Code must be amended to incorporate the need to screen customers, genetic sequences and address the cyberbiosecurity of biological life in digitalised form besides the physical biosecurity of laboratories which houses seedstocks from being stolen for malicious intent.